2021
DOI: 10.4149/gpb_2021013
|View full text |Cite
|
Sign up to set email alerts
|

An lncRNA-miRNA-mRNA-ceRNA network regulates intervertebral disc degeneration: A bioinformatics study based on the dataset analysis

Abstract: Intervertebral disc degeneration (IDD) leads to low back pain (LBP). This study aimed to determine the regulation of IDD by competing endogenous RNAs (ceRNAs). We obtained the GSE63492, GSE124272, and GSE129789 datasets from the Gene Expression Omnibus database. The changes of long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and mRNAs in IDD were characterized. The significantly changed mRNAs were subjected to protein-protein interaction analysis using the STRING database, and its functions and involved pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…LncRNA can affect the gene expression by competitively binding miRNAs, namely, ceRNA mechanism, which has been proved to play important and complicated roles in the initiation or progression of human diseases, including IDD [15,50,51] circular RNAs in the progression of IDD were described based on the latest literatures, which suggested that noncoding RNAs could serve as potential targets for the IDD treatment [53]. Moreover, a bioinformatic analysis conducted by Wang et al showed that miRNAs could function as novel targets for preventing and treating IDD by regulating their target genes [54].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA can affect the gene expression by competitively binding miRNAs, namely, ceRNA mechanism, which has been proved to play important and complicated roles in the initiation or progression of human diseases, including IDD [15,50,51] circular RNAs in the progression of IDD were described based on the latest literatures, which suggested that noncoding RNAs could serve as potential targets for the IDD treatment [53]. Moreover, a bioinformatic analysis conducted by Wang et al showed that miRNAs could function as novel targets for preventing and treating IDD by regulating their target genes [54].…”
Section: Discussionmentioning
confidence: 99%
“…miRTarBase is the key database, and all data have been verified experimentally. Genes predicted by miRTarBase and one of the other two databases were considered the target genes of DEMs [ 19 ]. Following the alignment of DEMs and DEGs, the Cytoscape software (v 3.9.1) was used to visualize the miRNA-mRNA regulatory network [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Micro-RNA list was imported to the miRWalk 3.0 online database to predict target genes, which comprises three sub-databases, namely, miRDB, Targetscan, and miRTarBase. Among them, miRTarBase was the unique database, of which all the data have been experimentally validated ( Fan et al, 2021 ). As a result, the genes predicted by miRTarBase w/o other two databases were considered to be the target genes of DEM.…”
Section: Methodsmentioning
confidence: 99%